Adhesion Materials: Friction Contribution to Bioinspired Mushroom‐Shaped Dry Adhesives (Adv. Mater. Interfaces 9/2017). Issue 9 (May 2017) - Hu, Hong; Tian, Hongmiao; Shao, Jinyou; Wang, Yue; Li, Xiangming; Tian, Yu; Ding, Yucheng; Lu, Bingheng
Abstract : Adhesion and friction are two general interactions of two solid surfaces in contact. In article number1700016, Jinyou Shao, Yu Tian, and co‐workers demonstrate the significance of friction in biologically inspired mushroom‐shaped dry adhesives, by modeling the crack governed interfacial behavior in adhesion failure. The authors also provide a proper guide on the structural dimensions for future artificial dry adhesive design, in which the friction contribution is considered quantitatively.